Binaural Hearing Rehabilitation Improves Speech Perception, Quality of Life, Tinnitus Distress, and Psychological Comorbidities. Issue 5 (June 2020) - Ketterer, Manuel Christoph; Häussler, Sophia-Marie; Hildenbrand, Tanja; Speck, Iva; Peus, Dominik; Rosner, Bastian; Knopke, Steffen; Graebel, Stefan; Olze, Heidi
Abstract : Objectives: To determine and compare the benefit of binaural hearing rehabilitation via cochlear implantation (CI) on speech perception, assessment of auditory abilities, tinnitus distress, health-related quality of life (HRQoL) and psychological comorbidities in patients suffering from asymmetric hearing loss (AHL) as well as bilaterally-deafened and sequentially bilaterally-implanted patients. Methods: 53 patients were implanted between 2011 and 2016. 24 AHL patients were implanted unilaterally, using a hearing aid on the other side. 29 bilaterally-deafened patients were sequentially implanted bilaterally. Speech perception, subjective hearing quality, HRQoL, tinnitus distress, anxiety, depressiveness, perceived stress level and coping abilities were evaluated before implantation, as well as 6 and 24 months postoperatively. Results: Before CI, AHL and bilaterally-deaf patients showed significant differences regarding assessment of auditory abilities, speech discrimination, tinnitus distress and HRQoL. 24 months after CI both groups significantly improved in those scales. We could not find a significant difference between the groups after 2 years. Tinnitus distress significantly decreased 6 and 24 months postoperatively in both groups. Conclusions: This study demonstrates the long-term benefit of binaural hearing rehabilitation in AHL and bilaterally-deaf patients not only regarding speech perception but also HRQoL, tinnitus distress and subjective hearing quality. Bilaterally-deafened patients present lower scores preoperatively, but they did not differ from AHL patients 2 years after CI. Up to now, this is the first study evaluating the outcome of CI in AHL patients compared to bilaterally-implanted patients and demonstrating the benefit of binaural hearing rehabilitation in these specific groups.